Measuring And Managing Dust And Nanoparticulates In Pyrometallurgical Processing - C. Copeland; S. Kawatra (Society for Mining, Metallurgy & Exploration, 2007)
Airborne particulates can be generated by combustion processes, comminution, or materials handling, and regulation of these particulates by EPA are becoming progressively more stringent. Regulations will soon include “nanoparticulates,” particles finer than 100 nanometers, which are believed to have significant health effects due to their high surface area and reactivity. Although it was argued that nanoparticulate concerns were only important for combustion, studies here have shown that material handling and comminution release significant quantities of nanoparticles into the air. Laboratory studies have shown that sodium metasilicate reduced airborne particles finer than 10 micrometers (PM10) by 86% and particles finer than 2.5 micrometers (PM2.5) by 80% for iron ore. Additional studies were conducted which revealed that nanoparticulate emissions were present in the types of operations conducted at pyrometallurgical facilities.